HAND2-AS1 targeting miR-1208/SIRT1 axis alleviates foam cell formation in atherosclerosis. (1st January 2022) - Ma, Lingyun; He, Shigui; Li, Helan; Zhang, Shengli; Yin, Yi
Abstract: The abnormally expressed long non-coding RNAs (lncRNAs) exert an important part in the occurrence and development of cardiovascular disease, however, their roles in atherosclerosis (AS) remains unknown. This work focused on investigating the role of HAND2 Antisense RNA 1 (HAND2-AS1) and the related mechanism. As a result, SIRT1 and HAND2-AS1 expression significantly decreased in plasma from patients with atherosclerotic plaques and macrophages originating from THP-1 induced by ox-LDL. Lentivirus mediated HAND2-AS1 overexpression markedly inhibited lipid absorption and deposition within foam cells originating from THP-1 macrophages. HAND2-AS1 endogenously sponged miR-128 and suppressed its activity via sequence complementation. Furthermore, HAND2-AS1 enhanced the expression of SIRT1 via binding to miR-128, thereby promoting ABCA1/G1 expression. Altogether, HAND2-AS1 targeting miR-1208/SIRT1 axis alleviates the formation of foam cells within AS. Besides, HAND2-AS1 may be used to be the possible anti-AS therapeutic target. Highlights: This work focused on investigating the role of HAND2 antisense RNA (HAND2-AS1) and the related mechanism. HAND2-AS1 targeting miR-1208/SIRT1 axis alleviates the formation of foam cells within AS. HAND2-AS1 has important effects on suppressing AS development and reveals the new SIRT1 regulatory mechanism.